Clinical profile of neonates with early onset sepsis - Masayu Ramadhani Polanunu, - (Ikatan Dokter Anak Indonesia - IDAI, 2016)
Background: Early-onset sepsis (EOS) remains one of the most common causes of neonatal morbidity and mortality. The clinical presentation in both preterm and term infant had wide variation There is limited data of it in Dr. Soetomo Hospital, Surabaya. Objective: To describe the clinical profile of early onset sepsis of neonates in Dr. Soetomo Hospital, Surabaya. Methods: This is a cross-sectional study of neonates, was born in Dr. Soetomo Hospital Surabaya between February to May 2016. The diagnosis is based on a combination of clinical presentation, complete blood count, C-reactive protein and blood cultures. Result: 235 neonates were born, 64 neonates were enrolled. Description data were taken such as 41 (64%) born aterm, 23 (36%) preterm. There were 27 (42%) neonates with birth weight >2500g, 33 (52%) neonates with birthweight 1500-2500g, 4 (6%) neonates with birthweight 1000-IS00g. The most common mode of delivery was 35 (55%) caesarean section and 28 (44%) born spontaneously. There were 42 (67%) neonates with premature rupture of membrane (PRoM), 13 (20%) neonates with jaundice, 1 (2%) with respiratory distress syndrome (RDS), 22 (34%) with asphyxia. From 64 neonates enrolled, 16 (25%) neonates with early onset sepsis and 48 (75%) neonates with late onset sepsis. Antibiotic given in 2 (13%) neonates. The range length of stay was 2-5 days. The outcome were 14 (88%) neonates alive and 2 (22%) discharge on request. Conclusion: Aterm neonates, with normal birth weight and delivered by caesarean section, with history of PRoM and RDS were susceptible ofEOS.